UNLOCKING BUSINESS GROWTH IN EAST JAVA'S SMES: THE SYNERGY OF KNOWLEDGE MANAGEMENT AND DYNAMIC CAPABILITIES FUELING INNOVATION AMBIDEXTERITY - Aini, Edlyn Khurotul; Yuliaji, Eliana Sandy (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research seeks to delve into the role of Knowledge Management Capability (KMC), Dynamic Capability (DC), and Ambidexterity Innovation (IA) in fostering Business Performance (BP) amongst Micro, Small, and Medium Enterprises (MSMEs) in the province of East Java. A quantitative approach was employed for this study, distributing questionnaires to various SMEs in East Java. Employing a non-probability sampling technique, 96 SMEs in East Java were selected as respondents based on Cochran's formula. The data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the interrelations among the constructs. This study provides a deeper understanding of how Knowledge Management Capability and Dynamic Capability contribute to Ambidexterity Innovation. The findings also suggest how Ambidexterity Innovation potentially boosts the Business Performance of SMEs in East Java. This research is distinguished by its emphasis on the interplay of Knowledge Management Capability and Dynamic Capability in influencing Innovation Ambidexterity within the context of East Java's SMEs.JEL: J24; O15; O32.